ILLUSTRATIVE MATERIAL AS A MEANS OF ACTIVATION COGNITIVE ACTIVITIES OF JUNIOR SCHOOLCHILDREN IN READING LESSONS (Pedagogy of Higher and Secondary Education, 2022)
The article examines the influence of extra textual means on intensification o f primary school children's cognitive activity on lessons dedicated to reading.